Analgesic efficacy and safety of the novel p38 MAP kinase inhibitor, losmapimod, in patients with neuropathic pain following peripheral nerve injury: a double‐blind, placebo‐controlled study. (14th December 2012) - Ostenfeld, T.; Krishen, A.; Lai, R.Y.; Bullman, J.; Baines, A.J.; Green, J.; Anand, P.; Kelly, M.
Abstract Background Inhibitors of p38 mitogen‐activated protein kinase are undergoing evaluation as a novel class of anti‐rheumatic drugs, by virtue of their ability to suppress the production of pro‐inflammatory cytokines. Emerging data suggests that they may also attenuate peripheral or central sensitization in neuropathic pain. A double‐blind, placebo‐controlled study was undertaken to evaluate the analgesic efficacy of losmapimod (GW856553), a novel p38α/β inhibitor, in subjects with neuropathic pain following traumatic peripheral nerve injury. Methods One hundred and sixty‐eight subjects with pain of at least moderate intensity (average daily score ≥4 on an 11‐point pain intensity numeric rating scale; PI‐NRS) at baseline were randomized to receive oral losmapimod, 7.5 mg BID or placebo for 28 days. Efficacy and safety assessments were undertaken at weekly clinic visits. Results The mean treatment difference for the change in average daily pain score from baseline to week 4 of treatment based on the PI‐NRS was −0.22 (95% CI −0.73, 0.28) in favour of losmapimod over placebo (p = 0.39). There were no statistically significant or clinically meaningful differences between the treatment groups over the 4‐week dosing period for either the primary or secondary efficacy variables. There were no unexpected safety or tolerability findings following dosing with losmapimod. Conclusions Losmapimod could not be differentiated from placebo in terms of a primary analgesia response in patients with pain following peripheral nerve injury. The lack of response could reflect inadequate exposure at central sites of action or differences between rodent and human with respect to the target or neuropathic pain mechanisms.